2022
DOI: 10.3390/jcm11040999
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Atresia in 2021: Epidemiology, Screening and Public Policy

Abstract: Biliary atresia (BA) is a rare newborn liver disease with significant morbidity and mortality, especially if not recognized and treated early in life. It is the most common cause of liver-related death in children and the leading indication for liver transplantation in the pediatric population. Timely intervention with a Kasai portoenterostomy (KPE) can significantly improve prognosis. Delayed disease recognition, late patient referral, and untimely surgery remains a worldwide problem. This article will focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 61 publications
0
29
0
1
Order By: Relevance
“…In this case, because of the short bowel, a short Roux loop was used to meet as much as possible the length of the intestinal tube to achieve total enteral nutrition. Success of KPE was defined as the clearance of jaundice and normalization of serum bilirubin 6 months after surgery ( 3 ). The infant's serum bilirubin reached the normal value 2 months after KPE surgery, and no cholangitis occurred during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, because of the short bowel, a short Roux loop was used to meet as much as possible the length of the intestinal tube to achieve total enteral nutrition. Success of KPE was defined as the clearance of jaundice and normalization of serum bilirubin 6 months after surgery ( 3 ). The infant's serum bilirubin reached the normal value 2 months after KPE surgery, and no cholangitis occurred during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Meconium peritonitis (MP) is a rare neonatal condition in which small bowel atresia is one of the underlying causes and needs to be urgently identified for surgical intervention ( 1 , 2 ). Combined with biliary atresia (BA), MP is even rarer, and early Kasai portoenterostomy (KPE) is essential for survival of the native liver and for the patient's survival ( 3 ). However, MP and IA sometimes require enterostomy.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of BA varies among regions. Indeed, previous studies reported that the incidence of BA is 1:15,000 to 1: 20,000 in live births in North America and Western Europe, 1 in 10,000 in Japan, 1 in 5,000 in Taiwan, and French Polynesia is that with the highest (1:3,000) (2,3). BA has three main clinical characteristics: jaundice lasting for more than 14 days, stools with a light color or clay stools and urine with a dark color.…”
Section: Introductionmentioning
confidence: 99%
“…Cholestatic jaundice is one of the major liver diseases in infants. Biliary atresia (BA) presents clinically in the first weeks of life with jaundice and acholic pale stools, the prototypical clinical features of an obstructive-type jaundice ( 1 ). Early diagnosis of BA and timely Kasai portoenterostomy (KPE) are correlated with favorable prognoses ( 2 ).…”
Section: Introductionmentioning
confidence: 99%